2011
DOI: 10.1590/s1809-29502011000200010
|View full text |Cite
|
Sign up to set email alerts
|

A classe da NYHA tem relação com a condição funcional e qualidade de vida na insuficiência cardíaca

Abstract: A insuficiência cardíaca (IC) é uma síndrome que se apresenta com crescente prevalência, podendo limitar o indivíduo quanto à capacidade físico-funcional, condição pulmonar e qualidade de vida. Este estudo tem como objetivo verificar as limitações pulmonares e físicas, bem como a qualidade de vida dos pacientes e compará-las com as classes funcionais da New York Heart Association (NYHA). Estudo transversal, com amostra de 66 pacientes (45 homens). Foram aplicados uma ficha de avaliação padronizada e o question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 28 publications
1
16
0
11
Order By: Relevance
“…It's known that the HF's main consequences regarding its symptoms are the dyspnea, the edema and the fatigue related to the physical limitation, which due to its pathophysiology there is a cardiac output reduction and an increase from both, lung and systemic venous pressure, leading to functional capability's deficits, the last being an important HD's mortality predictor and prognostic marker (DI NASO et al, 2011;DIAS et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It's known that the HF's main consequences regarding its symptoms are the dyspnea, the edema and the fatigue related to the physical limitation, which due to its pathophysiology there is a cardiac output reduction and an increase from both, lung and systemic venous pressure, leading to functional capability's deficits, the last being an important HD's mortality predictor and prognostic marker (DI NASO et al, 2011;DIAS et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among those methods there's the HF's functional classification from New York Heart Association (NYHA), which is based according with the symptoms presented by the patient when performing daily activities, varying from I to IV and the Veterans Specific Activity Questionnaire (VSAQ), which is an instrument able to measure the HF's physical limitation though metabolic equivalents (METs) (MYERS et al, 1994;DOMINGUES, 2010;DI NASO et al, 2011). Each MET represents an increase of 10% in the 1090 Physical limitation's impact in heart… SILVA, P. C. et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gyalai-Korpos et al (25) found that elderly people with CHF often present hospitalization time longer than 12 days, according to the New York Heart Association classification (NYHA>4), presence of one or more comorbidities, and associated chronic renal failure, as well as decreased pulmonary condition and physical functional capacity. These changes are associated with increased NYHA functional class, regardless of the values of the left ventricular ejection fraction, reflecting the impact of enhanced disease severity (26) . Therefore, CHF alone presents a number of factors that may explain the appearance of oropharyngeal dysphagia in the postoperative period of cardiac surgery, as reported by the studies listed in present review.…”
Section: Characterization Of Studiesmentioning
confidence: 93%
“…Many are the physical symptoms such as pain, chest discomfort, orthopnea, syncope and tachycardia. Beside those, swelling, loss of appetite, dry mouth, and daytime sleepiness, difficulty in maintaining a refreshing sleep, dyspnea and fatigue are commonly present (DI NASO et al, 2011;PELEGRINO et al, 2011).…”
Section: Introductionmentioning
confidence: 99%